2019
DOI: 10.1111/bjet.12854
|View full text |Cite
|
Sign up to set email alerts
|

Building pipelines for educational data using AI and multimodal analytics: A “grey‐box” approach

Abstract: Students' on‐task engagement during adaptive learning activities has a significant effect on their performance, and at the same time, how these activities influence students' behavior is reflected in their effort exertion. Capturing and explaining effortful (or effortless) behavior and aligning it with learning performance within contemporary adaptive learning environments, holds the promise to timely provide proactive and actionable feedback to students. Using sophisticated machine learning (ML) algorithms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 87 publications
3
87
0
Order By: Relevance
“…The term “Performance Analytics” includes data on the child’s performance and the countable product of their learning. Some examples are completion time, achievement or otherwise (1 or 0) of the assignment, speed of task resolution, the number of attempts or failures and the level of complexity of the problem‐solving process (Diago, González‐Calero & Arnau, 2019; Kosmas, Ioannou & Zaphiris, 2019; Sharma, Papamitsiou & Giannakos, 2019). Moreover, the study by Roberts, Chung and Parks (2016) measures “accuracy” as the ratio between correct and incorrect answers, and each game is evaluated according to a proficiency level.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The term “Performance Analytics” includes data on the child’s performance and the countable product of their learning. Some examples are completion time, achievement or otherwise (1 or 0) of the assignment, speed of task resolution, the number of attempts or failures and the level of complexity of the problem‐solving process (Diago, González‐Calero & Arnau, 2019; Kosmas, Ioannou & Zaphiris, 2019; Sharma, Papamitsiou & Giannakos, 2019). Moreover, the study by Roberts, Chung and Parks (2016) measures “accuracy” as the ratio between correct and incorrect answers, and each game is evaluated according to a proficiency level.…”
Section: Resultsmentioning
confidence: 99%
“…The availability and minimal intrusiveness of video cameras (compact cameras that may be smaller than a coin or incorporated in any mobile device), in conjunction with the potential of machine learning, makes them a device that is commonly used for studying aspects of understanding, achievement, emotions, attention and speech in MMLA research with children. Children’s actions can be recorded in a wide‐angle shot (Pérez, Martínez, Avila & Espinosa, 2018; Ramakrishnan et al ., 2019), with a 360° point‐of‐view multi‐camera system (Malmberg et al ., 2019) or with a webcam on top of a computer screen (Chen et al ., 2016; Pereira et al ., 2018; Sharma et al ., 2019) to analyse the emotions generated during the learning process automatically. Spikol and colleagues (2018) calculated the distance between the participants (recorded with a front camera), which they treated as a proxy for collaboration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has investigated student models of knowledge (Min et al ., 2017; Shute, Wang, Greiff, Zhao, & Moore, 2016; Spires, Rowe, Mott, & Lester, 2011) affect (Baker, D'Mello, Rodrigo, & Graesser, 2010; Botelho, Baker, & Heffernan, 2017; Henderson, Rowe, Mott, et al ., 2019). Several studies have demonstrated the value of incorporating multiple modalities of data generated from sensor‐based technologies (eg, facial expressions of emotions, eye gaze) to model students’ knowledge of complex topics (Blikstein & Worsley, 2016; Sharma, Papamitsiou, & Giannakos, 2019; Taub, Sawyer, Smith, et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%